Du rêve à la réalité, l’espace américain des écrivains d’expression anglaise du Proche-Orient arabe - Jacqueline Jondot (Anglophonia)
A number of Arab writers in the English language of the first half of the 20th century left the Middle East, considering the space offered them was too limited, to go the United States, thinking it would offer them numberless (physical, intellectual, moral...) opportunities, only to find that their new reality was just as limited (limited by a foreign community, a foreign language, loss of sense of direction...). Even though they can travel freely across the country, they are enclosed in an ideological discourse and in a textual space which is closely controlled. The promised land is physically, geographically, ideologically, metaphorically a closed space.